The Origin of the Elements - Lesher, Shelley R.; Arend, A. (Proceedings of the Wisconsin Space Conference, 2012)
There are about 35 nuclei found in nature, which are not susceptible to neutron capture and are explained by the p-process. The modeling for this process requires thousands of nuclear reactions involving both stable and unstable nuclei including (Î±,Î±), (Î±,p) and (Î±,Î³) reactions. In a recent experiment, the cross section of the reaction 120Te(Î±,p)123I was measured in the energy range of astrophysical interest for the p-process. The Î± beam from the Notre Dame FN Tandem Van de Graaff accelerator bombarded highly enriched self-supporting 120Te targets and the Î³-rays from the activated 123I was counted with a pair of Ge clover detectors in close geometry.Â 